School-Based Participatory Response for Reopening During the COVID-19 Pandemic: A Case Study of a Metropolitan High School Implementing the Health Promoting School - Kwon, Insook; Kang, Sunjoo; Kim, Jin Sun (Frontiers in Public Health, 2021)
Purpose: This study aimed to analyze how a private high school in Seoul developed and executed a “school disinfection strategy” to ensure the students’ right to study in a safe environment, and also analyze the lessons learned from this process. Methods: The was a case study of school health in a community-based school reopening during the COVID-19 pandemic. The target school was a 135-year-old private high school with 12 classes for each grade with a total of 1,000 students. Results: “School disinfection strategy” was set up at individual and class environment levels to protect students from the risk of infection. In addition, school health activities were carried out with a “personal protection safety belt” and “community protection safety belt” for effective implementation. To ensure a safe educational environment for high school students and to ensure smooth execution of face-to-face classes (in-person teaching), the “prevention safety belt strategy” was introduced in accordance with governmental guidelines to sequentially implement various preventive measures necessary to guarantee environmental safety of schools. Activating personal prevention safety belts by checking the symptoms of students when entering the school and during each class, and providing self-made disinfectants by spraying alcohol on wet-wipes were cost-effective and sustainable methods used in this school that can be applied easily in every school. Conclusions: The experience of developing a prevention safety belt strategy to adapt the guidelines of the local education office to the school situation was presented. Focusing on the school community, individual students, and teachers, the concept of prevention safety belts helped to unite and stimulate voluntary participation of students in the health promotion activities.